Phoenix from the Ashes: Fire, Torpor, and the Evolution of Mammalian Endothermy - Geiser, Fritz; Stawski, Clare; Wacker, Chris B.; Nowack, Julia (Frontiers in Physiology, 2017)
The asteroid strike causing global wildfires and the demise of dinosaurs and many other organisms at the Cretaceous-Paleogene (K-Pg) boundary ~65 Million years ago opened new niches for the evolution of modern mammalian lineages. While it is generally accepted that small ectotherms probably survived the post-impact winter that lasted for months because of their low metabolic rate (MR) and thus low food requirements, it is unknown how the small endothermic mammalian ancestors that were present at this time managed to do so. However, it is highly unlikely that a strictly homeothermic small terrestrial mammal with a constant high body temperature (Tb), high MR and consequently high food requirements would have had a chance, because they can survive without food for only a few days. It instead has been proposed that to survive the catastrophic K-Pg events, these small ancestral mammals must have been ‘heterothermic endotherms’ capable of using torpor for energy conservation. Torpor is characterised by substantial falls of MR and Tb often to fractions of basal MR, permitting small mammals to survive without food for up to an entire year. This hypothesis is supported by recent evidence revealing that the use of torpor increases substantially after fires, when availability of food and shelters is reduced, as would have been the case at the K-Pg boundary; charcoal and ash further enhance torpor in anticipation of prolonged detrimental conditions. Further, even at the beginning of the evolution of endothermy, heterothermy likely played a key role in the transition from ectothermy to endothermy. Our review will address current hypotheses and discuss the theoretical possibilities considering these and other new data with regard to two crucial evolutionary events: (i) the role of heterothermy in the evolution of avian and mammalian endothermy and (ii) the role of heterothermy in mammalian survival at the K-Pg boundary.